Survey of Memory Optimization Techniques for Embedded Systems - Oliveira, Lizandro; Mattos, Júlio C. B.; Brisolara, Lisane (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
Memory systems have been pointed out as a main source to the performance and power consumption of embedded software. Embedded systems require low-power consumption, so becomes interesting investigate memory optimization techniques for these systems. There are many techniques in the literature to reduce power/energy consumption and execution time of embedded systems. This work revises and discusses these techniques focusing on hardware and software optimizations.